2011
DOI: 10.1071/mu11001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in population trends of Kelp Gulls in northern Patagonia, Argentina

Abstract: Many populations of seabird species with opportunistic or generalist feeding habits have expanded worldwide, possibly because they are using additional food resources provided by human activities. The Kelp Gull (Larus dominicanus) is a generalist feeder that often feeds on urban and fish waste and its populations have been expanding in several regions of the southern hemisphere. In Patagonia, Argentina, it is the most abundant species of gull. However, population trends have been reported for only a few coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 34 publications
1
43
0
7
Order By: Relevance
“…Populations of many large gulls Larus spp. are increasing worldwide (Crawford et al 2009, Lisnizer et al 2011), due to cessation of control and/or increased human food subsidies, such as fisheries waste and open refuse tips (Bertellotti et al 2001, Yorio and Caille 2004). Gulls are often considered as an overabundant pest species (Blokpoel and Spaans 1991, Yorio et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Populations of many large gulls Larus spp. are increasing worldwide (Crawford et al 2009, Lisnizer et al 2011), due to cessation of control and/or increased human food subsidies, such as fisheries waste and open refuse tips (Bertellotti et al 2001, Yorio and Caille 2004). Gulls are often considered as an overabundant pest species (Blokpoel and Spaans 1991, Yorio et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Kelp Gulls are generalist and opportunistic feeders that take advantage of artificial food sources, such as fisheries discards and urban refuse (Yorio et al 2005). In Patagonia, Argentina, the Kelp Gull is the most abundant gull species (Yorio et al 1999), with an estimated total population of over 98,000 breeding pairs (Yorio et al 1998;Lisnizer et al 2011). Several studies have reported basic information about the size of Kelp Gull eggs (Williams et al 1984;Yorio and García Borboroglu 2002;Branco et al 2009).…”
mentioning
confidence: 99%
“…Kelp Gulls are the most abundant seabird species breeding on the island; their numbers have increased from 6,300 to 9,200 breeding pairs between 1995 and 2006 (Yorio et al 1998;Lisnizer et al 2011). Similar or higher population trends were observed for other Kelp Gull colonies in that coastal sector (Lisnizer et al 2011). …”
Section: Study Areamentioning
confidence: 60%
“…In several seabird species, fishery waste has been shown to affect breeding parameters, including egg size (Oro 1999). Supplemental food in the form of fisheries discards and urban refuse has also been mentioned as a possible factor that has driven population increases in the San Jorge Gulf area during the last 2 decades (Lisnizer et al 2011).…”
Section: Discussionmentioning
confidence: 99%